¿Quiénes son los rectores electos en las universidades estatales latinoamericanas? El caso de Chile y Venezuela: Who are the elected directors in Latin American state universities? The case of Chile and Venezuela - Ganga-Contreras, Francisco; Díaz-Barrios, Jazmín; Rivera-Díaz , Daniela (Universidad del Zulia, 2021)
Comparative analysis of the top managers (TM) elected in the public universities of Chile and Venezuela. Quantitative approach; documentary review of public data and self-administered questionnaire to directors in 28 universities. The coincidences and differences found talk about what the academic community of each country values when choosing its leaders. Age of promotion is 50, educators, not research oriented. Among the differences, the nonexistence of female rectors stands out in the Chilean case compared to more than 40% in Venezuela, and in training: the majority of Venezuelan MDs have a doctoral degree, and in Chile only 60%.